Optimalisasi Pemasaran Digital UMKM Lokal Berbasis Community Development di Dusun Melati Desa Sungai Itik - Wanda Ferdiansyah; Reza Cipta Saputra; Hafid Ramzi Ramadhan; Amanda Naya Dwigita; Muhammad Gusti Fernanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The PANDU Program (Village MSME Digital Marketing) was implemented in Melati Hamlet, Sungai Itik Village, to enhance the capacity of MSME actors in utilizing digital marketing to expand market reach. This study employed a mixed methods approach, combining qualitative methods to explore the context and needs of MSME actors and quantitative methods through pre-test and post-test measurements. Five MSMEs from various business sectors, ranging from processed foods to furniture, participated as program partners. The intervention was carried out through participatory training, technical assistance in creating social media accounts, designing visual promotional content, and strengthening business identity. The findings revealed a significant improvement in digital marketing skills, indicated by an average post-test score increase of 6,9 points compared to the pre-test. Behavioral changes were also observed, including the adoption of more structured digital promotion strategies and increased confidence in using technology. In conclusion, a hands-on practice approach combined with personalized mentoring proved effective in bridging the digital literacy gap among rural MSME actors.